JOHN F. KENNEDY DAN AHOK: KODE-KODE RETORIKA PEMIMPIN PUBLIK AGAMA MINORITAS - Murti, Desideria Cempaka Wijaya (Millah: Journal of Religious Studies, 2013)
Individual identity in politics is not a trivial matter. Identity is a signifier of meaning attached to a group. A Chinese politician will have a different symbolic meaning to majority of Indonesian people that considered him as foreigner. A similar case also occurred in the United States thata president is not only a leader of state and commander in chief during the war, but also as a symbol and ambassador for the country and the people who choose him. So that, it is feared that a leader from the minority is not able to become a symbol for the identities of the majority. Similar to Indonesia, a leader is expected to become a symbol for religion, ethnic, and tribal majority in the electoral area. However, with the current political developments, politicians from minority groups will have an “angel helper” because of the democratic system that separates religious affairs and public interest as well as the idea of equality and tolerance among religions.